2016
DOI: 10.1109/tvcg.2015.2467451
|View full text |Cite
|
Sign up to set email alerts
|

HOLA: Human-like Orthogonal Network Layout

Abstract: Fig. 1: Human, yFiles, and HOLA layouts of SBGN Glycolysis-Glygoneogensis pathway. It is clear that the human and the state-of-the-art layout algorithm from yFiles produce structurally quite different layouts. In this paper we explore the reasons why humans arrange such orthogonal network diagrams differently to standard algorithms and use this to inform the design of a new algorithm, HOLA (output shown right-most), that aims to produce more "human-like" layout.Abstract-Over the last 50 years a wide variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…[27]), compact node-placement is essential. A strong correllation between human preference and layout compactness is also observed in a recent study by Kieffer et al [29]. R2 -Proximity implies connectivity.…”
Section: Ultra-compact Grid Layoutsupporting
confidence: 78%
See 1 more Smart Citation
“…[27]), compact node-placement is essential. A strong correllation between human preference and layout compactness is also observed in a recent study by Kieffer et al [29]. R2 -Proximity implies connectivity.…”
Section: Ultra-compact Grid Layoutsupporting
confidence: 78%
“…This approach provides a regularity to the layout that leads the eye in a familiar and comfortable way [37]. Recent studies of network layout have shown that grid arrangements are memorable [35], when people arrange small diagrams themselves they prefer to place nodes at grid-points [42] and such placements are also preferred to TSM-based orthogonal layout [29].…”
Section: Introductionmentioning
confidence: 99%
“…E.g. sometimes a table is better than a visualization [2], a summary is better than a tag cloud [36], a deterministic graph layout vs. a spring-based layout [37], and so on.…”
Section: Do-it-yourself Visualization Critiquementioning
confidence: 99%
“…Many believe greater symmetry improves understandability and that, for example, force-directed layout promotes symmetry [1,2]. In the study of Kieffer et al, human subjects showed a preference for graphs with reflectional symmetry [3]. Likewise, Marriot et al confirmed that various layout featuresincluding symmetry -make graphs more memorable [4].…”
Section: Introductionmentioning
confidence: 99%